2014
DOI: 10.1021/am405905p
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Sensitive Novel Polymeric Resist Materials: Iterative Synthesis and Their EUV Fragmentation Studies

Abstract: Polymerization of (4-(methacryloyloxy)phenyl)dimethylsulfoniumtriflate (MAPDST), as a key monomer containing the radiation sensitive sulfonium functionality, with various other monomers such as methyl methacrylate (MMA), 4-carboxy styrene (STYCOOH), N-vinyl carbazole (NVK) in different molar ratios via free-radical polymerization method is described. This methodology led to the development of a small chemical library of six different radiation sensitive polymers for lithography applications. Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 41 publications
(50 reference statements)
4
69
0
Order By: Relevance
“…This result contrasted with the MAPDST homopolymer where new functionalities were needed to incorporate in the deconvolution to obtain a right fit after irradiation. 16 The C 1s XPS results match the QMS ones showing that an MAPDST-MMA copolymer may have a higher stability under 103.5 eV SR radiation excitation.…”
Section: Euv Photodynamic Studies Of N-cars Formulationsupporting
confidence: 60%
See 4 more Smart Citations
“…This result contrasted with the MAPDST homopolymer where new functionalities were needed to incorporate in the deconvolution to obtain a right fit after irradiation. 16 The C 1s XPS results match the QMS ones showing that an MAPDST-MMA copolymer may have a higher stability under 103.5 eV SR radiation excitation.…”
Section: Euv Photodynamic Studies Of N-cars Formulationsupporting
confidence: 60%
“…One of them is the C 5 H þ 9 fragment coincident with the CF þ 3 ion. In our previous publication, 16 it was found that in the case of the MAPDST homopolymer, SO þ 2 and SO þ intensities increased to reach a maximum and then decreased to zero in a few minutes; the m∕z ¼ 69 increased to a maximum and then decreased to the background level. The new contribution of m∕z ¼ 69 observed corresponds to the desorption of CF þ 3 ions produced by 103.5 eV photon excitation.…”
Section: Euv Photodynamic Studies Of N-cars Formulationmentioning
confidence: 81%
See 3 more Smart Citations